2013
DOI: 10.1016/j.bbamem.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

EpCAM: Structure and function in health and disease

Abstract: Injection of tumor cells in mice more than 30 years ago resulted in the discovery of an epithelial antigen, later defined as a cell adhesion molecule (EpCAM). Although EpCAM has since evoked significant interest as a target in cancer therapy, mechanistic insights on the functions of this glycoprotein have been emerging only very recently. This may have been caused by the multitude of functions attributed to the glycoprotein, its localization at different subcellular sites and complex posttranslational modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
243
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(251 citation statements)
references
References 144 publications
4
243
0
4
Order By: Relevance
“…Increasing clinical evidence has confirmed that EpCAM is involved in cancer progression and is associated with a poor prognosis. [7][8][9] More evidence suggested that EpCAM played a critical factor in tumor development, progression, and metastasis. 10,11 For example, EpCAM is frequently overexpressed in patients with acute myeloid leukemia (AML), with EpCAM + leukemic cells exhibiting enhanced chemoresistance and oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing clinical evidence has confirmed that EpCAM is involved in cancer progression and is associated with a poor prognosis. [7][8][9] More evidence suggested that EpCAM played a critical factor in tumor development, progression, and metastasis. 10,11 For example, EpCAM is frequently overexpressed in patients with acute myeloid leukemia (AML), with EpCAM + leukemic cells exhibiting enhanced chemoresistance and oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…20 A mega-analysis of the gene expression database using the online software tool ExAtlas 21 revealed that derepressed genes ($2-fold) were largely nonhematopoietic genes ( Figure 3B). We compared ChIP-seq data for H3K9me3 levels with RNA-seq data in GMPs.…”
mentioning
confidence: 99%
“…Figure 3a shows the bright field and fluorescent images of stained PC-3 cells without fixation (GS&NF), which suggested the existence of anti-Human EpCAM Alexa Fluor 488. , which may result from the endocytosis of anti-EpCAM after binding with surface antigen EpCAM. In addition, a significant difference in σcytoplasm for GNS&NF vs. GS&NF cells was observed, further suggesting the possibility of surface antigen endocytosis and the triggering of the downstream signal pathways [26].…”
Section: Resultsmentioning
confidence: 91%